“Red Spitz Tumor” on the Ear: Case Report and Review of the Literature - Liang Y; Yu Y; Luan W; Xu J (Dove Medical Press, 2022)
YeHua Liang,1 Yijia Yu,1 Weimin Luan,2 Jinghong Xu1 1Department of Plastic Surgery, The First Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang, People's Republic of China; 2Department of NeuroSurgery, Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang, People's Republic of ChinaCorrespondence: Jinghong Xu, Tel/Fax +86-571-87236307, Email 1304017@zju.edu.cnAbstract: Spitz nevus (SN) is a benign melanocytic lesion with cytologic and architectural atypia. It is sometimes difficult to distinguish SNs from atypical Spitz tumor (AST), Spitz melanoma, or conventional melanoma. SNs frequently develop in Caucasians and appear on the skin of the head and lower extremities. Lesions on the ear in Asian populations are rare. Here, we report a "red Spitz tumor" on the ear of a Chinese 18-year-old boy. Dermoscopic examination revealed possibly malignant features presented as polymorphous vessels along with central white area, pseudo-network depigmentation and atypical peripheral globular pattern. The results of histopathological examination strongly suggested that the neoplasm was a compound SN and no recurrences or metastases occurred during 1-year follow-up post-surgery. Further, we review the literature on 4 previously reported cases of SN on the ear and summarize the main points of SN diagnosis and differential diagnosis with atypical Spitz tumors and melanoma.Keywords: Spitz nevus, atypical Spitz tumors, hypo-pigmented Spitz nevus, malignant melanoma